PENGEMBANGAN MEDIA GAME EDUKASI WORDWALL PADA MATERI INDONESIAKU KAYA BUDAYA MATA PELAJARAN IPAS SISWA KELAS IV GUGUS VI KECAMATAN BATURITI - Gusti Ayu Sri Diana Fanny; L Heny Nirmayani; Putu Eka Sastrika Ayu (Widyajaya: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
This study aims to develop a Wordwall Educational Game media with the theme "My Indonesia is Rich in Culture". The focus is on the Natural and Social Sciences (IPAS) subject for fourth grade students at SDN Gugus VI, Baturiti District. The development of this media is expected to be valid and practical in stimulating students' interest and enthusiasm for learning. Thus, it is expected to be able to increase understanding and active participation of participants in the learning process. The approach taken in this development is the Research and Development method which applies the ADDIE model, including 5 stages: Analysis, Design, Development, Implementation, and Evaluation. The subjects in this study consisted of three experts for instrument assessment, six experts for product testing, one teacher with a Master's degree category IV, and four teachers and fourth grade students at SDN Gugus VI, Baturiti District. Data were obtained through observational, interviews, and questionnaires. The findings of this research and development show that the validity level of the Wordwall Educational Game media is classified as very valid, with a media validity score of 0.93, a learning validity score of 0.94, and a language validity score of 0.94. Furthermore, the results of practicality tests conducted by teachers and students also show that the overall practicality of the teachers reached 95.5%, while the students reached 90%. This development research indicates that the developed product has a high level of practicality. Therefore, the Wordwall Educational Game media can be considered an effective innovative learning tool in increasing student engagement in science learning and supporting the achievement of learning objectives in the digital era.